Activity of Dexamethasone Therapy on Pro-Inflammatory Cytokines Profile of Balb/c Mice with Biliary Atresia - Qonitatul Khasanah; Muhaimin Rifa'i (Biotropika: Journal of Tropical Biology, 2014)
ABSTRACT Biliary atresia is a neonatal obstructive cholangiopathy that progresses to end-stage liver disease. Dexamethasone is one of synthetic glucocorticoid which has function as an anti-inflammatory agent. Here, we investigated whether dexamethasone could modulate the immune activity in mice strain Balb/c with biliary atresia based on the change of quantity of IFN-γ and TNF-α as a pro-inflammatory molecules. This study consists of 2 stages. The first stage is pre-condition which is made the biliary duct become fibrosis by injecting 20 µl of phosphate buffered saline containing 1.5 x 106 fluorescence-forming units Rhesus Rotavirus (RRV) subcutaneously on first day (24 hours) after the mice was born. The second stage is injection with dexamethasone with dose 0,5 mg/kg BW subcutaneously on the 7th-14th day and 14th-21st day. The clinical effect of dexamethasone is investigated on 14th and 21st day by flow cytometry method. Data were analyzed using Kruskal-Wallis test (p<0,05) and Mann-Whitney test using SPSS 16 for Windows. Rotavirus injection subcutaneously was proven to stimulate the production of proinflammatory cytokines, especially in the third week of termination. The result indicated an increasing number of proinflammatory cytokines such as IFN-γ and TNF-α after RRV injection but after injection of dexamethasone the number of those cytokines is decreased. It can be understood that dexamethasone has a capability to reduce the effect of inflammation regard to the decrease of proinflammatory cytokines. Keywords : Biliary atresia, Dexamethasone, Inflammation, Obstructive, Rhesus Rotavirus